Possible Bacteria Pathogens Found in the Internal Surface of Ladies Handbags in Umuahia, Abia State, South-Eastern Nigeria - Nwankwo, E.O.; Okochi, D.I (UMYU Journal of Microbiology Research)
Bacteria including the pathogenic species have been isolated from fomites, these organisms are sometimes multidrug resistant and are of public health concern. It is therefore important to isolate and identify potential bacterial pathogens associated with the internal surface of ladies handbags, in Umuahia, Abia state. One hundred and forty swabbed samples were collected from the ladies hand bags in different groups of individuals which include; Nurses, civil servants, students and market women. Also the handbags from which the samples were collected includes: Leather, Cotton, Nylon and Polyester and velvet handbags. The bags were swabbed with sterile swab sticks and inoculated on different types of culture media and incubated at 37oC for 24 hours. Bacterial isolates were identified using standard microbiological methods including biochemical tests before subjecting isolates to different antimicrobial sensitivity test that was carried out by disc diffusion method. The following bacteria were isolated from the internal surface of the handbags, Coagulase Negative Staphylococci 6(2.6%), Escherichia coli 36(15.7%), Klebsiella spp. 14(6.1%), Staphylococcus aureus 49(21.3%), Bacillus spp. 48(20.9%), Pseudomonas aeruginosa 5(2.2%), Proteus spp. 5(2.2%), streptococcus spp. 31(13.5), Micrococcus spp. 20(8.7%), Salmonella spp. 3(1.3%) and Enterococcus faecalis 13(5.7%). Most of the isolates were sensitive to levofloxacin, gentamicin, norfloxacin, ciprofloxacin and resistant to ampiclox, chloramphenicol and erythromycin. Potentially pathogenic bacteria resistant to multiple antibiotics can be spread by hand contact from ladies handbags.